2012 38th IEEE Photovoltaic Specialists Conference 2012
DOI: 10.1109/pvsc.2012.6317694
|View full text |Cite
|
Sign up to set email alerts
|

InAs/AlGaAs quantum dot intermediate band solar cells with enlarged sub-bandgaps

Abstract: -In the last decade several prototypes of intermediate band solar cells (IBSCs) have been manufactured. So far, most of these prototypes have been based on InAs/GaAs quantum dots (QDs) in order to implement the IB material. The key operation principles of the IB theory are two photon subbandgap (SBG) photocurrent, and output voltage preservation, and both have been experimentally demonstrated at low temperature. At room temperature (RT), however, thermal escape/relaxation between the conduction band (CB) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…This requires that thermal carrier escape from the QDs be suppressed [22] and that non-radiative processes in the cells be minimised. Recent results of reduced thermal escape due to a higher bandgap (AlGaAs) host material [23], and high QD-IBSC V oc s due to improved material quality [24] are promising in this regard. Second, the subbandgap photocurrent must be improved significantly by increasing subbandgap photon absorption in the QD array.…”
Section: Introductionmentioning
confidence: 99%
“…This requires that thermal carrier escape from the QDs be suppressed [22] and that non-radiative processes in the cells be minimised. Recent results of reduced thermal escape due to a higher bandgap (AlGaAs) host material [23], and high QD-IBSC V oc s due to improved material quality [24] are promising in this regard. Second, the subbandgap photocurrent must be improved significantly by increasing subbandgap photon absorption in the QD array.…”
Section: Introductionmentioning
confidence: 99%
“…These improvements to the design have been proposed in [2], where it was demonstrated that the thermal activation energy of these InAs/AlGaAs QDs is about 250 meV higher than the energies found in the literature for InAs/GaAs QD, and almost 140 meV higher than the activation energy obtained in our previous InAs/GaAs QD-IBSC prototypes including a strain-relief-layer. It has been possible to resolve spectrally the contribution of the IB-CB transition to the sub-bandgap photocurrent [ Fig.…”
Section: Methodsmentioning
confidence: 57%
“…12 A better match to the solar spectrum can be achieved by replacing GaAs with Al x Ga 1Àx As spacers. 13 With a maximum lattice mismatch of only 0.1%, Al x Ga 1Àx As can be easily grown on a GaAs substrate, and a similar strain-induced Stranski-Krastanov growth mode can be expected for InAs QDs on this alloy. There are only a few studies of InAs QDs grown on Al 1Àx Ga x As, particularly by MOVPE, and a careful investigation is needed.…”
Section: Introductionmentioning
confidence: 91%